2011
DOI: 10.4103/0971-6866.92105
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale meta-analysis of genetic studies in ischemic stroke: Five genes involving 152,797 individuals

Abstract: BACKGROUND:Ischemic stroke descent has a genetic basis. Stroke represents a complex trait, which is assumed to be polygenic. On this topic, the role of a wide number of candidate genes has been investigated in stroke through association studies.MATERIALS AND METHODS:We performed a literature-based systematic review of genetic association studies in stroke abound several populations. Odds ratios (ORs) and 95% confidence intervals (CIs) were determined for each gene-disease association. Following a review of 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Hamzi K., et al . performed a meta-analysis, which revealed that prothrombin and MTHFR were risk factors in Indian patients with ischemic stroke 31 . CIS protein is important for the complement cascade and plays a role in the regulation of immune adhesion 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Hamzi K., et al . performed a meta-analysis, which revealed that prothrombin and MTHFR were risk factors in Indian patients with ischemic stroke 31 . CIS protein is important for the complement cascade and plays a role in the regulation of immune adhesion 32 .…”
Section: Discussionmentioning
confidence: 99%
“…One third occur in patients younger than 65 years [3]. Etiologies include atrial fibrillation with embolization [3], hypertension, diabetes mellitus, cervicocerebral stenosis [1,2,4], cerebral venous thrombosis [5] and a hypercoaguable state [4,5,6,7,8,9]. …”
Section: Discussionmentioning
confidence: 99%
“…The most frequent candidate polymorphism associated with the risk of cerebral stroke include ACE, factor V Leiden, MTHFR, prothrombin G20210A and apolipoprotein E [8]. The thrombogenic risk factor increases with the cumulative existence of the variant mutations: the gene-dose effect [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that supplementation with Riboflavin in hypertensive patients carrying the homozygous genotype mutant 677TT of MTHFR, without other cardiovascular diseases, has considerably improved the value of systolic blood pressure, paving the way for personalized medicine [ 16 ]. It is worth noting, that numerous studies investigated the relationship between the C677T polymorphism of MTHFR and many diseases, including breast cancer [ 17 , 18 ], colorectal cancer [ 19 ], ischemic stroke [ 20 , 21 ], inflammatory bowel disease [ 22 ] and hypertension [ 7 , 23 , 24 ]. In the light of the limited data on the variants of the MTHFR and hypertension in our population, and the role of vitamin B2 in the improvement of blood pressure in hypertensive patients with a mutant variant of the MTHFR gene, this case–control study was carried out to investigate the association of 677C > T polymorphism of MTHFR with the risk of hypertension in a sample of the Moroccan population.…”
Section: Introductionmentioning
confidence: 99%